﻿Notulae to the Italian alien vascular flora: 16 - Gabriele Galasso; Gianniantonio Domina; Michele Adorni; Claudia Angiolini; Lorenzo Baccheschi; Gianluigi Bacchetta; Giulio Barone; Fabrizio Bartolucci; Giacomo Calvia; Sergio Costantini; Alba Cuena-Lombraña; Giuseppe De Fine; et al. (Italian Botanist, 2023)
In this contribution, new data concerning the distribution of vascular flora alien to Italy are presented. It includes new records and status changes from casual to naturalized for Italy or for Italian administrative regions. Nomenclatural and distribution updates, published elsewhere, and corrections are provided as supplementary material.